Sn-Zn / AC particle and preparation method and application thereof

By loading SNO2 and ZNSNO3 on the surface of activated carbon, SN-Zn/AC particles are prepared to solve the problem of low particle electrode catalytic efficiency in the existing technology, realizing the rapid electrical degradation and removal of organic pollutants, improving processing efficiency and improving processing efficiency and improving processing efficiency and improving processing efficiency and improving processing efficiency and improving processing efficiency and improving processing efficiency and improving processing efficiency and improving the efficiency and efficiency stability.

CN119349721AActive Publication Date: 2025-01-24GUANGDONG UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411654724.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-24
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

In the prior art, the catalytic efficiency of particle electrodes is slow and cannot meet the need for rapid treatment of organic pollutants.

Method used

By loading SnO2 and ZnSnO3 on the surface of activated carbon, Sn-Zn/AC particles are prepared, and their high oxygen evolution potential and excellent charge transfer ability are used to form an anode protective layer to enhance charge transfer efficiency and catalytic activity.

Benefits of technology

It significantly improves the charge transfer efficiency and catalytic activity on the surface of Sn-Zn/AC particles, achieves rapid electrocatalytic degradation and removal of organic pollutants, and improves treatment efficiency and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349721A_ABST
    Figure CN119349721A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrocatalyst materials, and particularly relates to Sn-Zn / AC particles and a preparation method and application thereof. The Sn-Zn / AC particle is successfully prepared by loading SnO2 and ZnSnO3 on the surface of the activated carbon. Wherein SnO2 and ZnSnO3 are uniformly distributed on the surface of the activated carbon, so that not only is the particle stability improved, but also the service life of the activated carbon is prolonged; the introduction of Zn not only improves the densification degree of SnO2, but also effectively reduces the charge transfer resistance of the particle electrode. The excellent charge transfer ability of SnO2 and ZnSnO3 is combined, efficient generation of active free radicals is promoted, and therefore the catalytic degradation removal rate of an electro-catalysis system constructed on the basis of Sn-Zn / AC particles on organic pollutants is remarkably increased. In addition, the preparation method of the Sn-Zn / AC particles further has the advantages of being easy to operate, high in controllability, low in energy consumption and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalytic materials, and more specifically, relates to a Sn-Zn / AC particle and a preparation method and application thereof. Background Art

[0002] According to statistics, about one million tons of dyes are produced worldwide each year, of which more than 15% are released into the environment as pollutants in industrial wastewater. Dye wastewater entering the ecological environment can cause mutagenicity and carcinogenicity to organisms, as well as damage to the brain, central nervous system and reproductive system. Dyes can be divided into reactive dyes, acid dyes, basic dyes, etc., among which basic dyes can also be called cationic dyes. Commonly used cationic dyes include methylene blue, rhodamine B, Congo red, etc. Methylene blue is a cationic dye widely used in textile, leather, pharmaceutical and food industries. It is present in wastewater and cannot be biologically removed. It is toxic and carcinogenic, posing a threat to human health and the environment. In order to reduce the harm caused by dye wastewater, the main wastewater treatment methods include: physical method, chemical method, biological method and advanced oxidation process. Among them, traditional treatment methods such as physical method, chemical method and biological method have long adsorption contact time, and the removal of dye wastewater is not thorough. In addition, these traditional technologies are prone to secondary pollution due to the use of chemicals in the treatment process, and the removal cost is high. Advanced oxidation technology (AOPs) is highly regarded as a novel and reliable method that can effectively remove persistent dyes and has the advantages of rapid response, thoroughness, high efficiency and low pollution.

[0003] Commonly used advanced oxidation technologies include Fenton oxidation technology, ozone oxidation technology, wet oxidation technology, photocatalytic oxidation technology, electrocatalytic oxidation technology, three-dimensional electrocatalytic oxidation technology, persulfate oxidation technology, etc. Among them, electrocatalytic oxidation technology has the characteristics of simple operation, green environmental protection, and mild reaction conditions. Traditional two-dimensional electrochemistry has the disadvantages of pollutant mass transfer limitation, small specific surface area, low current efficiency, high energy consumption, and low removal efficiency during the treatment process. The three-dimensional electrochemical advanced oxidation process has a higher specific surface area, mass transfer distance, and higher pollutant removal efficiency, and can completely mineralize organic pollutants that cannot be removed biologically. It is considered to be an efficient dye wastewater treatment method. The core of three-dimensional electrochemical technology is the particle electrode. In the traditional electrochemical reactor, conductive particles are filled between the cathode and the anode. These particles are polarized under the action of the electrostatic field generated by the cathode and the anode. A large number of dotted micro-areas will be formed on the surface of the polarized particles. These micro-areas are equivalent to tiny electrodes, namely "particle electrodes". The two ends of these particle electrodes carry opposite charges, thus forming a large number of third electrodes in the entire reaction system. These particle electrodes can independently perform functions similar to those of traditional electrodes in electrolytic cells, such as promoting electron transfer, accelerating chemical reactions, etc. For example, Pu et al. (Pu Y, Zhao F, Chen Y, et al. Enhanced Electrocatalytic Oxidation of Phenol by SnO2-Sb2O3 / GAC Particle Electrodes in a Three-Dimensional Electrochemical Oxidation System[J]. Water, 2023, 15(10): 1844.) disclosed a SnO2-Sb2O3 / GAC particle electrode that can remove 99.65% of phenol in 180 min and has good stability. However, the electrocatalytic removal efficiency of the SnO2-Sb2O3 / GAC particle electrode is still relatively slow and cannot meet the removal requirements of rapid processing. Its electrocatalytic efficiency still needs to be further improved. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art particle electrodes, that is, the catalytic efficiency is still relatively slow and cannot meet the demand for rapid removal of organic pollutants, and to provide a Sn-Zn / AC particle.

[0005] Another object of the present invention is to provide a method for preparing the Sn-Zn / AC particles.

[0006] Another object of the present invention is to provide an electrocatalytic system constructed based on the above Sn-Zn / AC particles.

[0007] Another object of the present invention is to provide the use of the above Sn-Zn / AC particles or the above electrocatalytic system in degrading and removing organic pollutants.

[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0009] The invention protects a Sn-Zn / AC particle. The Sn-Zn / AC particle uses activated carbon as a carrier and mainly loads SnO2 and ZnSnO3.

[0010] The Sn-Zn / AC particles prepared by the present invention use activated carbon (AC) as a carrier, and mainly load SnO2 and ZnSnO3. Among them, AC exhibits high conductivity, stable chemical properties and excellent ability to catalyze active free radicals. The carrier not only loads the active component SnO2, but also contains a small amount of ZnSnO3. SnO2 is selected for its high oxygen evolution potential, excellent conductivity and chemical stability; and the loading of ZnSnO3 not only covers the surface of AC, but also penetrates into some internal gaps to form an anode protection layer. This protective layer effectively inhibits Sn 4+ The dissolution of Sn-Zn / AC particles improves the densification of SnO2 and reduces the charge transfer resistance of the particle electrode, thereby significantly enhancing the charge transfer efficiency on the surface of Sn-Zn / AC particles. Under the action of the electric field, Sn-Zn / AC particles are more easily polarized to form microelectrodes. The increase of these microelectrodes and their higher oxygen evolution potential effectively inhibit the oxygen evolution side reaction during the reaction process, prompting the generation of more hydroxyl radicals (·OH) in the system. Thanks to the synergistic effect of Sn-Zn / AC particles and active free radicals, pollutants can be quickly electrocatalytically degraded and removed, showing the excellent catalytic activity and stability of Sn-Zn / AC particles.

[0011] The present application protects a method for preparing the above Sn-Zn / AC particles, comprising the following steps:

[0012] Adding activated carbon to Sn 4+ 、Zn 2+ After being fully impregnated in the impregnation solution, the Sn-Zn / AC particles are fully calcined at 400-650°C to obtain Sn-Zn / AC particles.

[0013] This application combines the impregnation method and the calcination method to prepare Sn-Zn / AC particles, and successfully achieves Sn 4+ and Zn 2+ The good loading on the AC surface significantly improves the performance of the particles. 4+ and Zn 2+It can be evenly loaded on the AC surface; the modified layer formed after calcination not only has better corrosion resistance, but also forms ZnSnO3 with excellent charge transfer ability, which significantly improves the oxygen evolution potential of the prepared Sn-Zn / AC particles and further improves the electrocatalytic removal ability of organic pollutants.

[0014] Preferably, the activated carbon is pretreated activated carbon, and the pretreatment includes water washing, alkali washing, acid washing and drying. In the pretreatment process of activated carbon, water washing can remove large particles of impurities and dust attached to the surface of the material; alkali washing can effectively remove grease and alkali-soluble substances; acid washing can further remove impurity metal oxide films that may exist on the surface of the material; drying makes the material reach a suitable state, which is conducive to the subsequent loading of metals.

[0015] Furthermore, the activated carbon is preferably activated carbon particles (AC particles). AC particles are beneficial for the adsorption and enrichment of pollutants due to their large specific surface area and rich pore structure, thereby effectively increasing the concentration of pollutant substrates at the particle electrode interface, thereby accelerating the removal process of organic pollutants.

[0016] Furthermore, the mesh size of the AC particles is 1-3.

[0017] Furthermore, the pretreatment includes water washing, alkali washing, acid washing and drying.

[0018] Furthermore, the water washing includes soaking and cleaning.

[0019] Furthermore, the soaking is to add the AC particles into water and soak them.

[0020] Furthermore, the washing is to repeatedly wash the soaked AC particles 3 to 5 times until the aqueous solution is clear and transparent.

[0021] Specifically, the water washing includes soaking the AC particles in water and repeatedly washing them 3 to 5 times until the aqueous solution is clear and transparent.

[0022] Furthermore, the alkaline washing includes filtering, stirring and rinsing.

[0023] Furthermore, the filtering is to filter the washed AC particles through a sieve.

[0024] Furthermore, the stirring is to add the filtered AC particles into 2000 mL of 0.1-1 mol / L sodium hydroxide solution and stir at 200-500 rpm / min for 10-60 min.

[0025] Furthermore, the rinsing is to repeatedly rinse the AC particles with water for 3 to 5 times after the stirring to remove the residual alkaline solution.

[0026] Specifically, the alkali washing includes filtering the washed AC particles with a sieve, adding the filtered AC particles into 2000mL of 0.1-1mol / L sodium hydroxide solution, stirring at 200-500rpm / min for 10-60min, and repeatedly rinsing with water for 3-5 times after the stirring to remove the residual alkali solution.

[0027] Furthermore, the pickling includes stirring and rinsing.

[0028] Furthermore, the stirring is to add the alkali-washed AC particles into 2000 mL of 0.1-1 mol / L hydrochloric acid solution and stir at 200-500 rpm / min for 10-60 min.

[0029] Furthermore, the rinsing is to repeatedly rinse the AC particles after stirring with water for 3 to 5 times to remove residual acid.

[0030] Specifically, the acid washing comprises adding the alkali washed AC particles into 2000 mL of 0.1-1 mol / L hydrochloric acid solution, stirring at 200-500 rpm / min for 10-60 min, and repeatedly washing with water for 3-5 times after stirring to remove residual acid.

[0031] Furthermore, the drying comprises heating the acid-washed AC particles to 30-100° C., drying for 6-24 hours to a constant weight, and cooling to obtain pretreated AC particles.

[0032] Furthermore, the method for preparing the impregnation solution comprises the following steps:

[0033] Containing Sn 4+ 、Zn 2+ The solution is mixed with citric acid and alcohol solvent to obtain the impregnation solution.

[0034] Furthermore, the Sn 4+ The tin salt is selected from tin chloride, potassium stannate, sodium stannate or a hydrate of any of the above tin salts.

[0035] Furthermore, the Sn 4+ The concentration is 0.05~0.6mol / L.

[0036] Furthermore, the Zn 2+ The zinc salt is selected from zinc nitrate, zinc sulfate, zinc chloride or a hydrate of any of the above zinc salts.

[0037] Furthermore, the Zn 2+ The concentration is 0.05~0.6mol / L.

[0038] Furthermore, the Sn 4+ With Zn 2+The molar ratio of Sn is 1:(0.083-12). 4+ 、Zn 2+ The content and distribution of these elements in the solution can better achieve the uniform distribution of these elements on the surface of AC particles.

[0039] Preferably, the Sn 4+ With Zn 2+ The molar ratio of SnO2 to ZnSnO3 is 1:(5-10). Within this ratio range, the synergistic effect of SnO2 and ZnSnO3 is greatly enhanced, so Sn-Zn / AC particles can efficiently catalyze the removal of organic pollutants. At the same time, this synergistic effect promotes the formation of a stable anode protection layer, effectively inhibiting Sn 4+ The dissolution of the particles is slowed down, maintaining the structural stability of the particles and delaying the performance degradation.

[0040] Preferably, the Sn 4+ With Zn 2+ The molar ratio is 1:(5~8).

[0041] More preferably, the Sn 4+ With Zn 2+ The molar ratio is 1:6.

[0042] Furthermore, the Sn-containing 4+ 、Zn 2+ The solvent of the solution includes one or more of ethanol, methanol and propanol.

[0043] Furthermore, the alcohol solvent includes one or more of ethylene glycol, propylene glycol, and butylene glycol. Alcohol solvents can react with metal ions (Sn 4+ 、Zn 2+ ) form complexes to enhance the stability of metal ions in the solution and prevent them from precipitating prematurely, thereby ensuring the concentration and activity of metal ions in the impregnation solution.

[0044] Furthermore, the mass of the pretreated AC particles is 0.5-10 g.

[0045] Furthermore, the volume of the impregnation liquid is 0.1-0.5L.

[0046] Furthermore, the full impregnation method includes static impregnation and shaking impregnation. Full impregnation can promote the deep penetration of electrolyte into the particles, ensuring full activation of the material.

[0047] Furthermore, the static soaking is soaking for 0.5 to 5 hours under static conditions.

[0048] Furthermore, the shaking soaking condition is shaking at 50-150 rpm / min for 0.5-3 hours.

[0049] Specifically, the sufficient immersion includes soaking for 0.5 to 5 hours at rest and then soaking for 0.5 to 3 hours at 50 to 150 rpm / min.

[0050] Furthermore, the step of fully impregnating further includes drying.

[0051] Furthermore, the drying includes oil bath heating and vacuum drying.

[0052] Preferably, the oil bath heating condition is heating at 50-105° C. for 0.5-3 h.

[0053] Preferably, the vacuum drying condition is drying at 50-105° C. for 0.5-5 h.

[0054] Preferably, the temperature of the sufficient calcination is 400-600°C. 4+ 、Zn 2+ When the temperature is too high (>650℃) or too low (<400℃), this effect may cause the structure of tin-zinc oxide to be destroyed, which in turn increases the charge transfer resistance and causes the oxygen evolution potential to decrease, ultimately affecting the removal rate of organic pollutants.

[0055] Furthermore, the sufficient calcination time is 1 to 5 hours.

[0056] The present invention protects an electrocatalytic system, which includes a cathode, an anode, a third electrode and an electrolyte, wherein the third electrode includes the Sn-Zn / AC particles obtained above.

[0057] The electrocatalytic system based on Sn-Zn / AC particles prepared by the present invention has a large specific surface area and strong adsorption activity. In the electrocatalytic process of the system, a variety of active species with strong oxidative activity are generated, such as hydroxyl radicals (·OH) and sulfate radicals (SO4 - ·) etc. The electrocatalytic system has the advantages of simple operation, green environmental protection, mild reaction conditions, rapid, thorough, high efficiency and low pollution.

[0058] Furthermore, the electrocatalytic system also includes an electrolyte, an electrolytic cell, a power supply, and an agitator. The container of the electrolytic reactor is a cylindrical electrolytic cell of 300 to 600 mL. The positive electrode and the negative electrode are placed vertically in the reactor at a distance of 20 to 60 mm. A certain amount of modified activated carbon particles are dispersed and filled in the reactor in a fluidized state, and move freely under the action of the magnetic rotor. Using the electrode clamp and the power cord connection device and the DC regulated power supply, the reactor is placed in a heat-collecting constant temperature heating agitator, and the reaction is carried out at a constant speed at a water temperature of 25 to 35°C.

[0059] Furthermore, the positive electrode and the negative electrode are platinum-plated titanium electrodes.

[0060] Furthermore, the electrolyte is 10 to 50 mmol / L Na2SO4.

[0061] Furthermore, the voltage of the electrolytic cell is 3-7V.

[0062] Furthermore, the power supply is a DC regulated power supply.

[0063] Furthermore, the agitator is a heat-collecting constant-temperature agitator.

[0064] Furthermore, the stirring rate of the stirrer is 200-600 rpm / min.

[0065] Further, as a preferred embodiment, the experimental process of the electrocatalytic system includes the following steps:

[0066] The removal rate of methylene blue (MB) was used as an indicator to evaluate the effect of Sn-Zn / AC particles on the removal of dye wastewater. Use an electronic balance to accurately weigh MB solid and other required drugs, add ultrapure water to fully dissolve, and transfer the solution to a 200mL volumetric flask for fixed volume. Before the experiment, a certain amount of particles were soaked in a 10-50mg / L MB solution for 0.5-3h to eliminate the influence of particle electrode adsorption; the initial conditions were set to a constant voltage of 3-7V, a sodium sulfate concentration of 10-50mmol / L, pH=2-7, a particle electrode filling amount of 0.5-3g, a constant speed, and a reaction time of 30-100min, including 5-30min of non-electric adsorption and 20-80min of electrocatalytic reaction; every 5-20min, 2-5mL of liquid water sample was extracted with a syringe, filtered through a 0.22μm water filter membrane, and transferred to a sample tube, and relevant parameters were set and the absorbance value of the water sample was detected.

[0067] The present invention protects the use of the above Sn-Zn / AC particles or the above electrocatalytic system in degrading and removing organic pollutants.

[0068] The principle of degradation and removal of organic pollutants of the present invention is as follows: the electrocatalytic system constructed based on Sn-Zn / AC particles degrades and removes MB through the combined action of direct electro-oxidation and indirect electro-oxidation. In the direct electrocatalytic process, the Sn-Zn / AC particles form microelectrodes under the action of the electric field, and MB is adsorbed on the surface of the main electrode and the particle microelectrode under the dual action of physical adsorption and electro-adsorption, and then oxidized and decomposed in the anode area of ​​the main electrode and the particle microelectrode. In the indirect reaction process, driven by voltage and Coulomb force, the anode area of ​​the main electrode and the particle microelectrode has strong oxidizing properties (i.e., electron-withdrawing ability), while the cathode area has reducing properties (i.e., electron-donating ability). Therefore, the anode area can convert water or hydroxide (OH - ) is oxidized to generate a large amount of ·OH, while the cathode area can reduce dissolved oxygen to generate H2O2. - · Coexistence, · OH can also promote a small amount of hydrogen sulfate (HSO4 - ) is converted to SO4 - ·. In ·OH, SO4 - Under the combined action of water and H2O2, MB is gradually decomposed into small molecular organic matter and finally mineralized into water and carbon dioxide.

[0069] Furthermore, the organic pollutant is an organic pollutant containing a benzene ring.

[0070] Furthermore, the organic pollutants containing benzene rings include one or more of methylene blue, rhodamine B, and methyl orange.

[0071] Preferably, the organic pollutant containing a benzene ring is methylene blue.

[0072] Compared with the prior art, the present invention has the following beneficial effects:

[0073] The present invention successfully prepares a Sn-Zn / AC particle by loading SnO2 and ZnSnO3 on the surface of activated carbon. The uniform distribution of SnO2 and ZnSnO3 on the surface of activated carbon not only improves the stability of the particles, but also prolongs their service life; the introduction of Zn not only improves the densification degree of SnO2, but also effectively reduces the charge transfer resistance of the particle electrode. The combination of SnO2 and ZnSnO3's excellent charge transfer ability promotes the efficient generation of active free radicals, thereby significantly improving the catalytic degradation and removal rate of organic pollutants by the electrocatalytic system constructed based on Sn-Zn / AC particles. In addition, the preparation method of Sn-Zn / AC particles also has many advantages such as simple operation, strong controllability, and low energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Figure 1 This is a flow chart of the preparation of Sn-Zn / AC particles in Example 1.

[0075] Figure 2 The Sn-Zn / AC particles prepared in Example 1 are applied to a reactor device of an electrocatalytic system.

[0076] Figure 3 This is an experimental setup for applying the Sn-Zn / AC particles prepared in Example 1 to an electrocatalytic system.

[0077] Figure 4 (a) is a SEM image of the pretreated AC particles prepared in Example 1 at a magnification of 250 times, and (b) is a SEM image of the pretreated AC particles at a magnification of 1000 times.

[0078] Figure 5 (a) is a SEM image of the Sn-Zn / AC particles prepared in Example 1 at a magnification of 250 times, and (b) is a SEM image of the Sn-Zn / AC particles at a magnification of 1000 times.

[0079] Figure 6 (a) The total element distribution spectrum of the pretreated AC particles prepared in Example 1 and (b) the total element distribution spectrum of the Sn-Zn / AC particles.

[0080] Figure 7 XRD diagrams of the Sn-Zn / AC particles prepared in Example 1 and Comparative Example 3 and the pretreated AC particles.

[0081] Figure 8 This is the XRD pattern of the Sn-Zn powder prepared in Comparative Example 5.

[0082] Fig. 9 Schematic diagram of the catalytic principle of the electrocatalytic system constructed based on Sn-Zn / AC particles in Example 1.

[0083] Fig.10 (a) is a graph showing the MB removal rate variation over time of the electrocatalytic systems constructed in Example 1, Comparative Examples 2 to 5, and Comparative Examples 6 to 10, and (b) is a comparison graph showing the energy consumption of the electrocatalytic systems in Example 1, Comparative Example 2, and Comparative Example 4 for fixed removal of 80% MB.

[0084] Fig.11 The MB removal rate curves of the particles prepared in Example 1 and Comparative Example 4 in different organic pollutants changing with time.

[0085] Fig.12 The EPR detection spectrum (a) of the Sn-Zn / AC particles prepared in Example 1 detecting the activated persulfate system at 5 min and the EPR detection spectrum (b) at 10 min.

[0086] Fig.13The linear voltammetric curves of the particles prepared in Example 1 and Comparative Example 3 are shown.

[0087] Fig.14 The electrochemical impedance spectra of the particles prepared in Example 1 and Comparative Example 3 are shown.

[0088] Fig.15 It is the Tafel slope diagram of the particles prepared in Example 1 and Comparative Example 3.

[0089] Fig.16 This is a bar graph of the MB removal rate of the Sn-Zn / AC particles prepared in Example 1 after 5 cycles. DETAILED DESCRIPTION

[0090] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0091] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0092] Figure 4 (a) indicates Figure 4 Figure (a) in the figure; Figure 4 (b) indicates Figure 4 The naming of other figures is similar to that of Figure (b) in the figure.

[0093] Example 1 A Sn-Zn / AC particle, an electrocatalytic system, and a preparation method and application thereof

[0094] 1. Preparation of Sn-Zn / AC particles

[0095] The preparation flow chart of Sn-Zn / AC particles is as follows Figure 1 As shown, it specifically includes the following steps:

[0096] S1. Pretreatment of activated carbon (AC) particles: ① Water washing: Take 10 g of 2 mesh particle size AC particles were placed in a 2000 mL beaker, soaked in deionized water and repeatedly washed three times until the aqueous solution was visually clear and transparent; ② alkali washing: 2000 mL of 0.1 mol / L sodium hydroxide solution was prepared, the AC particles washed in step ① were filtered through a sieve and put into the alkali solution, stirred at a speed of 250 rpm / min for 30 min with an electric stirrer, and rinsed repeatedly with ultrapure water three times after stirring to remove residual alkali solution; ③ acid washing: 2000 mL of 0.1 mol / L hydrochloric acid solution was prepared, the particles washed in step ② were added to the hydrochloric acid solution, stirred at a speed of 250 rpm / min for 30 min with an electric stirrer, and soaked in ultrapure water and repeatedly rinsed three times after stirring to remove residual acid; ④ drying: the cleaned AC particles were placed in an electric hot air drying oven, set at 60°C, and air dried for 24 h until the AC particles were constant weight, and the dried AC particles were cooled to room temperature to obtain pretreated AC particles.

[0097] S2. Preparation of impregnation solution: 1.753 g of tin tetrachloride pentahydrate, 8.925 g of zinc nitrate hexahydrate, and 15 mL of ethanol were added to a beaker and stirred for 15 min to dissolve them completely and form a transparent solution to obtain liquid A; 2.8815 g of citric acid, 8 mL of ethylene glycol, and 15 mL of ethanol were added to a beaker and stirred for 15 min to dissolve them completely and form a transparent solution to obtain liquid B; liquid B was poured into liquid A and stirred for 1 h to obtain Sn 4+ The concentration is 0.1 mol / L, Zn 2+ The concentration of the impregnation solution is 0.6mol / L.

[0098] S3. Preparation of Sn-Zn / AC particles: Use an electronic balance to weigh 10g of AC particles pretreated in step S1 and add them to a conical flask, then add the impregnation solution prepared in step S2 and let it soak for 2h. After soaking, put the conical flask into a water bath constant temperature oscillator and oscillate at 150rpm / min for 1h to completely soak the pretreated AC particles. Transfer the AC particles after shaking to a 50mL ceramic crucible, place the crucible in a heat-collecting constant temperature heating magnetic stirrer, use an oil bath for heating, set the oil bath temperature to 105℃, and heat for 1h; then transfer the crucible to an electric blast drying oven and dry it at 105℃ for 2h; after the particles are dried and cooled, wrap the ceramic crucible with tin foil, put the crucible in a box furnace, and roast it at 600℃ for 3h. After cooling, Sn-Zn / AC particles are obtained.

[0099] 2. Construction and application of an electrocatalytic system

[0100] The schematic diagram of the electrocatalytic system is shown in Figure 2-3 As shown, first, Figure 2Schematic diagram of a reactor device in an electrocatalytic system, which consists of a platinum-titanium electrode 1, an electrolyte 2, and Sn-Zn / AC particles 3; Figure 3 This is a schematic diagram of the complete electrocatalytic system structure, which mainly consists of a DC regulated power supply ①, a heat-collecting constant temperature heating stirrer ②, a stainless steel electrode clamp and a platinum-titanium electrode ③ and Sn-Zn / AC particles ④. Among them, the main plates of this experiment are all platinum-plated titanium electrodes, and the plate spacing is 2 to 6 cm; the Sn-Zn / AC particles are filled in a discrete state; the experiment is carried out in an environment where the electrolyte Na2SO4 concentration is 5 to 50 mmol / L; the platinum-titanium electrode is connected to a DC power supply through an electrode clamp and a power cord; the electrolytic cell is placed on a magnetic stirrer table, the cell voltage is 3 to 7 V, and the speed of the magnetic rotor is 200 to 600 rpm.

[0101] The application method of the electrocatalytic system comprises the following steps:

[0102] Use an electronic balance to accurately weigh 0.2g of methylene blue (MB) solid, add ultrapure water to fully dissolve, and transfer the solution to a 200mL volumetric flask to set the volume for use. Before the experiment, take 2g of the Sn-Zn / AC particles obtained in step 1 above and soak them in a 40mg / L MB solution for 1h to eliminate the influence of the adsorption of the particle electrode (i.e., Sn-Zn / AC particles); the initial conditions are set to a constant voltage of 5V, a Na2SO4 concentration of 20mmol / L, and a pH of 4. The particle electrode is filled with 2g of the above-mentioned soaked Sn-Zn / AC particles, the rotation speed is constant, and the reaction time is set to 70min, including 10min of non-electric adsorption and 60min of electrocatalytic reaction; every 10min, use a syringe to extract 3.5mL of liquid water sample, filter it through a 0.22μm water filter membrane, and transfer it to the sample tube, set relevant parameters, and detect the absorbance value of the water sample.

[0103] Example 2 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0104] The difference from Example 1 is that in step S2, Sn 4+ The concentration was changed from 0.1mol / L to 0.05mol / L, Zn 2+ The concentration was changed from 0.6 mol / L to 0.4 mol / L, and the calcination time at 600 °C was changed from 3 h to 2 h.

[0105] The other steps and conditions are the same as those in Example 1.

[0106] Example 3 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0107] The difference from Example 1 is that in step S2, Sn 4+ The concentration was changed from 0.1mol / L to 0.2mol / L, Zn2+ The concentration was changed from 0.6 mol / L to 0.05 mol / L, and the calcination time at 600 °C was changed from 3 h to 4 h.

[0108] The other steps and conditions are the same as those in Example 1.

[0109] Example 4 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0110] The difference from Example 1 is that in step S2, Sn 4+ The concentration was changed from 0.1mol / L to 0.4mol / L, Zn 2+ The concentration was changed from 0.6 mol / L to 0.1 mol / L, and the calcination time at 600 °C was changed from 3 h to 5 h.

[0111] The other steps and conditions are the same as those in Example 1.

[0112] Example 5 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0113] The difference from Example 1 is that in step S2, Sn 4+ The concentration was changed from 0.1mol / L to 0.6mol / L, Zn 2+ The concentration was changed from 0.6 mol / L to 0.2 mol / L, and the calcination time at 600 °C was changed from 3 h to 1 h.

[0114] The other steps and conditions are the same as those in Example 1.

[0115] Example 6 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0116] The difference from Example 1 is that in step S2, Sn 4+ The concentration was changed from 0.1 mol / L to 0.05 mol / L, and the calcination temperature was changed from 600°C to 650°C.

[0117] The other steps and conditions are the same as those in Example 1.

[0118] Example 7 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0119] The difference from Example 1 is that in step S2, Zn 2+ The concentration was changed from 0.6 mol / L to 0.05 mol / L, the calcination temperature was changed from 600°C to 650°C, and the calcination time was changed from 3 h to 4 h.

[0120] The other steps and conditions are the same as those in Example 1.

[0121] Example 8 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0122] The difference from Example 1 is that in step S2, Sn 4+ The concentration was changed from 0.1mol / L to 0.2mol / L, Zn 2+ The concentration was changed from 0.6 mol / L to 0.1 mol / L, the calcination temperature was changed from 600°C to 650°C, and the calcination time was changed from 3 h to 5 h.

[0123] The other steps and conditions are the same as those in Example 1.

[0124] Example 9 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0125] The difference from Example 1 is that in step S2, Sn 4+ The concentration was changed from 0.1mol / L to 0.4mol / L, Zn 2+ The concentration was changed from 0.6 mol / L to 0.2 mol / L, the calcination temperature was changed from 600°C to 650°C, and the calcination time was changed from 3 h to 1 h.

[0126] The other steps and conditions are the same as those in Example 1.

[0127] Example 10 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0128] The difference from Example 1 is that in step S2, Sn 4+ The concentration was changed from 0.1mol / L to 0.6mol / L, Zn 2+ The concentration was changed from 0.6 mol / L to 0.4 mol / L, the calcination temperature was changed from 600°C to 650°C, and the calcination time was changed from 3 h to 2 h.

[0129] The other steps and conditions are the same as those in Example 1.

[0130] Example 11 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0131] The difference from Example 1 is that in step S2, Sn 4+ The concentration was changed from 0.1mol / L to 0.05mol / L, Zn 2+ The concentration was changed from 0.6 mol / L to 0.2 mol / L, the calcination temperature was changed from 600°C to 500°C, and the calcination time was changed from 3 h to 5 h.

[0132] The other steps and conditions are the same as those in Example 1.

[0133] Example 12 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0134] The difference from Example 1 is that in step S2, Zn 2+ The concentration was changed from 0.6 mol / L to 0.4 mol / L, the calcination temperature was changed from 600°C to 500°C, and the calcination time was changed from 3 h to 1 h.

[0135] The other steps and conditions are the same as those in Example 1.

[0136] Example 13 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0137] The difference from Example 1 is that in step S2, Sn 4+ The concentration was changed from 0.1 mol / L to 0.2 mol / L, the calcination temperature was changed from 600°C to 500°C, and the calcination time was changed from 3 h to 2 h.

[0138] The other steps and conditions are the same as those in Example 1.

[0139] Example 14 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0140] The difference from Example 1 is that in step S2, Sn 4+ The concentration was changed from 0.1mol / L to 0.4mol / L, Zn 2+ The concentration was changed from 0.6 mol / L to 0.05 mol / L, and the calcination temperature was changed from 600°C to 500°C.

[0141] The other steps and conditions are the same as those in Example 1.

[0142] Example 15 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0143] The difference from Example 1 is that in step S2, Sn 4+ The concentration was changed from 0.1mol / L to 0.6mol / L, Zn 2+ The concentration was changed from 0.6 mol / L to 0.1 mol / L, the calcination temperature was changed from 600°C to 500°C, and the calcination time was changed from 3 h to 4 h.

[0144] The other steps and conditions are the same as those in Example 1.

[0145] Example 16 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0146] The difference from Example 1 is that in step S2, Sn 4+The concentration was changed from 0.1mol / L to 0.05mol / L, Zn 2+ The concentration was changed from 0.6 mol / L to 0.1 mol / L, and the calcination temperature was changed from 600°C to 400°C.

[0147] The other steps and conditions are the same as those in Example 1.

[0148] Example 17 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0149] The difference from Example 1 is that in step S2, Zn 2+ The concentration was changed from 0.6 mol / L to 0.2 mol / L, the calcination temperature was changed from 600°C to 400°C, and the calcination time was changed from 3 h to 4 h.

[0150] The other steps and conditions are the same as those in Example 1.

[0151] Example 18 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0152] The difference from Example 1 is that in step S2, Sn 4+ The concentration was changed from 0.1mol / L to 0.2mol / L, Zn 2+ The concentration was changed from 0.6 mol / L to 0.4 mol / L, the calcination temperature was changed from 600°C to 400°C, and the calcination time was changed from 3 h to 5 h.

[0153] The other steps and conditions are the same as those in Example 1.

[0154] Example 19 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0155] The difference from Example 1 is that in step S2, Sn 4+ The concentration was changed from 0.1 mol / L to 0.4 mol / L, the calcination temperature was changed from 600°C to 400°C, and the calcination time was changed from 3 h to 1 h.

[0156] The other steps and conditions are the same as those in Example 1.

[0157] Example 20 A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0158] The difference from Example 1 is that in step S2, Sn 4+ The concentration was changed from 0.1mol / L to 0.6mol / L, Zn 2+ The concentration was changed from 0.6 mol / L to 0.05 mol / L, the calcination temperature was changed from 600°C to 400°C, and the calcination time was changed from 3 h to 2 h.

[0159] The other steps and conditions are the same as those in Example 1.

[0160] Comparative Example 1: A Sn-Zn / AC particle, an electrocatalytic system, and its preparation method and application

[0161] The difference from Example 1 is that in step S2, the calcination temperature is changed from 600°C to 700°C.

[0162] The other steps and conditions are the same as those in Example 1.

[0163] Comparative Example 2 A particle, an electrocatalytic system, and its preparation method and application

[0164] The difference from Example 1 is that in step S3, Sn is not doped when preparing the particles. 4+ 、Zn 2+ , AC particles, which are direct electrocatalytic systems (E systems).

[0165] The other steps and conditions are the same as those in Example 1.

[0166] Comparative Example 3: AC particles, electrocatalytic system, preparation method and application thereof

[0167] The difference from Example 1 is that in step S3, Sn is not doped when preparing the particles. 4+ and Zn 2+ , which is an AC particle electrocatalytic system (E-AC system).

[0168] The other steps and conditions are the same as those in Example 1.

[0169] Comparative Example 4: A Sn / AC particle, an electrocatalytic system, and a preparation method and application thereof

[0170] The difference from Example 1 is that in step S3, Zn is not doped when preparing the particles. 2+ , which is a Sn / AC particle electrocatalytic system (E-Sn / AC system).

[0171] The other steps and conditions are the same as those in Example 1.

[0172] Comparative Example 5: A Sn-Zn powder, an electrocatalytic system, and a preparation method and application thereof

[0173] The difference from Example 1 is that in step 1, AC particles are not doped when preparing particles, and a Sn-Zn powder electrocatalytic system (E-Sn-Zn system) is used.

[0174] 1. Preparation of Sn-Zn powder

[0175] S1. Preparation of impregnation solution: 1.753 g of tin tetrachloride pentahydrate, 8.925 g of zinc nitrate hexahydrate, and 15 mL of ethanol were added to a beaker and stirred for 15 min to dissolve them completely and form a transparent solution to obtain liquid A; 2.8815 g of citric acid, 8 mL of ethylene glycol, and 15 mL of ethanol were added to a beaker and stirred for 15 min to dissolve them completely and form a transparent solution to obtain liquid B; liquid B was poured into liquid A and stirred for 1 h to obtain Sn 4+ The concentration is 0.1 mol / L, Zn 2+ The concentration of the impregnation solution is 0.6mol / L.

[0176] S2. Preparation of Sn-Zn powder: transfer the impregnation solution obtained in step S1 to a 50mL ceramic crucible, place the crucible in a heat-collecting constant temperature heating magnetic stirrer, heat it in an oil bath, set the oil bath temperature to 105°C, and heat for 1 hour; then transfer the crucible to an electric blast drying oven and dry it at 105°C for 2 hours; after it is dried and cooled, wrap the ceramic crucible with tin foil, place the crucible in a box furnace, and roast it at 600°C for 3 hours. After cooling, obtain Sn-Zn powder.

[0177] 2. Construction and application of an electrocatalytic system

[0178] The schematic diagram of the electrocatalytic system is shown in Figure 2-3 As shown, first, Figure 2 Schematic diagram of a reactor device in an electrocatalytic system, which consists of a platinum-titanium electrode 1, an electrolyte 2, and Sn-Zn powder 3; Figure 3 This is a schematic diagram of the complete electrocatalytic system structure, which mainly consists of a DC regulated power supply ①, a heat-collecting constant temperature heating stirrer ②, a stainless steel electrode clamp and a platinum-titanium electrode ③ and Sn-Zn powder ④. Among them, the main plates of this experiment are all platinum-plated titanium electrodes, and the plate spacing is 2 to 6 cm; the Sn-Zn powder is filled in a discrete state; the experiment is carried out in an environment where the electrolyte Na2SO4 concentration is 5 to 50 mmol / L; the platinum-titanium electrode is connected to a DC power supply through an electrode clamp and a power cord; the electrolytic cell is placed on a magnetic stirrer table, the cell voltage is 3 to 7 V, and the speed of the magnetic rotor is 200 to 600 rpm.

[0179] The application method of the electrocatalytic system comprises the following steps:

[0180] Use an electronic balance to accurately weigh 0.2g of methylene blue (MB) solid, add ultrapure water to fully dissolve, and transfer the solution to a 200mL volumetric flask for fixed volume. The initial conditions are set to a constant voltage of 5V, a sodium sulfate concentration of 20mmol / L, and a pH of 4. The particle electrode is filled with 2g of Sn-Zn powder prepared above. The rotation speed is constant, and the reaction time is set to 70min, including 10min of non-electric adsorption and 60min of electrocatalytic reaction. Every 10min, 3.5mL of liquid water sample is extracted with a syringe, filtered through a 0.22μm water filter membrane, and transferred to a sample tube. The relevant parameters are set and the absorbance value of the water sample is detected.

[0181] Comparative Example 6: A Sn-Fe / AC particle, an electrocatalytic system, and a preparation method and application thereof

[0182] The difference from Example 1 is that in step S2, zinc nitrate hexahydrate is replaced by ferric chloride to obtain Sn-Fe / AC particles.

[0183] The other steps and conditions are the same as those in Example 1.

[0184] Comparative Example 7: A Sn-Cu / AC particle, an electrocatalytic system, and its preparation method and application

[0185] The difference from Example 1 is that in step S2, zinc nitrate hexahydrate is replaced with copper sulfate to obtain Sn-Cu / AC particles.

[0186] The other steps and conditions are the same as those in Example 1.

[0187] Comparative Example 8: A Sn-Mn / AC particle, an electrocatalytic system, and a preparation method and application thereof

[0188] The difference from Example 1 is that in step S2, zinc nitrate hexahydrate is replaced with manganese sulfate to obtain Sn-Mn / AC particles.

[0189] The other steps and conditions are the same as those in Example 1.

[0190] Comparative Example 9: A Sn-Ag / AC particle, an electrocatalytic system, and a preparation method and application thereof

[0191] The difference from Example 1 is that in step S2, zinc nitrate hexahydrate is replaced with silver nitrate to obtain Sn-Ag / AC particles.

[0192] The other steps and conditions are the same as those in Example 1.

[0193] Comparative Example 10: A Sn-V / AC particle, an electrocatalytic system, and a preparation method and application thereof

[0194] The difference from Example 1 is that in step S2, zinc nitrate hexahydrate is replaced with sodium metavanadate to obtain Sn-V / AC particles.

[0195] The other steps and conditions are the same as those in Example 1.

[0196] Experimental Example Determination of the physical and chemical properties of particles and electrocatalytic systems

[0197] 1. SEM Characterization

[0198] The AC particles and Sn-Zn / AC particles pretreated in Example 1 were characterized by SEM. The results were as follows: Figure 4 and Figure 5 shown.

[0199] from Figure 4 (a) It can be seen that the surface of the pretreated AC particles has a rough porous layer and a large number of gullies and pits. Figure 4 (b) It can be seen that the inside of the pits on the surface of the activated carbon is filled with a large number of tiny holes of different sizes, indicating that it has strong adsorption properties.

[0200] from Figure 5 It can be seen that the surface morphology of AC particles after metal loading has changed dramatically. Figure 4 Compared with the AC particles magnified 250 times in (a), Figure 5 The surface of the Sn-Zn / AC particles shown in (a) is covered by an oxide film, and the number of surface pits is significantly reduced. Figure 5 (b) It can be seen that the micropores inside the pits on the surface of the AC particles are basically covered, compared with Figure 4 (b) The surface of the AC particles of Sn-Zn / AC particles is smoother and flatter, and the metal oxides not only cover the outer surface of the activated carbon, but also cover part of the internal pores. The coverage of these metal films can prevent organic pollutants from accumulating on the surface of AC particles, extending the service life of Sn-Zn / AC particles.

[0201] 2. EDS characterization

[0202] EDS characterization (Energy Dispersive X-ray Spectroscopy) is based on the fact that when a substance is bombarded by a high-energy electron beam, it will produce X-rays of specific energy. These X-rays have characteristic spectra based on their original atoms. By detecting the energy and density of these characteristic X-rays, the types of elements present in the sample and their content can be determined. EDS characterization was performed on the AC particles and Sn-Zn / AC particles pretreated in Example 1. Figure 6As can be seen from (a), the surface elements of the pretreated AC particles are mainly in the form of C and O, without obvious Sn and Zn peaks. The content of C accounts for 97wt%, and the content of O accounts for 3wt%, and neither contains Sn or Zn elements, indicating that there is almost no Sn or Zn element in the AC particles before loading. Figure 6 As can be seen from (b), the elements in the total number spectrum of the Sn-Zn / AC particle distribution map are mainly in the form of C, Sn, Zn, and O, of which the content of C accounts for 83.2wt%, the content of O accounts for 4.8wt%, the content of Sn is 9.9wt%, and the content of Zn is 2.1wt%, which is relatively low. The Sn:Zn atomic ratio on the surface of Sn-Zn / AC particles is 2.57:1, which is close to the theoretical atomic ratio (2:1) in the impregnation solution, proving that Sn and Zn elements are successfully loaded on the surface of AC particles.

[0203] 3. XRD characterization

[0204] The crystal structures of the AC particles and Sn-Zn / AC particles pretreated in Example 1 were studied at scanning angles of 10° to 80°. Figure 7 As shown in the figure, both the pretreated AC particles and Sn-Zn / AC particles exhibited characteristic broad peaks of activated carbon at 2θ=23° and 42.7° (PDF#26-1076), which are the main crystalline phases of activated carbon. After loading metal elements, the intensity of the diffraction peaks of activated carbon weakened, while the Sn-Zn / AC particles exhibited sharp characteristic diffraction peaks at 2θ=26.6°, 33.89° and 51.78°, corresponding to the (110), (101) and (211) crystal planes of SnO2 (PDF#41-1445, PDF#99-0024, PDF#77-0447, PDF#71-0652), indicating that the Sn element mainly exists in the form of SnO2. However, no peak of ZnO was detected in the X-ray diffraction pattern, which may be due to the low loading of Zn element, uniform dispersion or the formation of other low-content compounds.

[0205] To further confirm the existence form of Zn element, the mixed impregnation solution composed of Sn and Zn was dried and calcined without adding AC particles to obtain Sn-Zn powder (Comparative Example 5), and X-ray diffraction analysis was performed. The results are as follows: Figure 8As shown. The analysis found that the main peak is SnO2, and it may contain ZnSnO3 (PDF#99-0024 and PDF#28-1486). Combining the results of SEM and EDS analysis, it can be obtained that although the surface of the particles contains Zn elements, ZnO with a high boiling point (2360°C) is not detected. At the same time, considering that the Zn element is not easy to dissipate during the roasting process. It can be seen that the Zn element and the Sn element combine to form a ZnSnO3 compound. Therefore, the active substances on the surface of Sn-Zn / AC particles are mainly composed of SnO2 and ZnSnO3.

[0206] 4. Catalytic principle of the electrocatalytic system based on Sn-Zn / AC particles

[0207] The electrocatalytic system based on Sn-Zn / AC particles degrades and removes MB through the combined action of direct and indirect electrooxidation ( Fig. 9 ). In the direct electrocatalytic process, Sn-Zn / AC particles form microelectrodes under the action of the electric field, and MB is adsorbed on the surface of the main electrode and the particle microelectrode under the dual action of physical adsorption and electroadsorption, and then oxidized and decomposed in the anode area of ​​the main electrode and the particle microelectrode. In the indirect reaction process, driven by voltage and Coulomb force, the anode area of ​​the main electrode and the particle microelectrode has strong oxidizing properties (i.e., electron-withdrawing ability), while the cathode area has reducing properties (i.e., electron-donating ability). Therefore, the anode area can convert water or hydroxide (OH - ) is oxidized to generate a large amount of ·OH, while the cathode area can reduce dissolved oxygen to generate H2O2. - · Coexistence, · OH can also promote a small amount of hydrogen sulfate (HSO4 - ) is converted to SO4 - ·. In ·OH, SO4 - Under the combined action of water and H2O2, MB is gradually decomposed into small molecular organic matter and finally mineralized into water and carbon dioxide.

[0208] 5. Determination of organic pollutant removal efficiency and energy consumption analysis

[0209] The absorbance value of the water sample is closely related to the removal rate. The larger the absorbance value, the higher the concentration of a substance in the water sample; the smaller the absorbance value, the lower the concentration of the substance. Therefore, the concentration of the removed substance will change during the removal process, so the removal rate of the substance is calculated by the change in absorbance. Assume that the absorbance of the initial water sample is A0, and the absorbance of the water sample after removal is A1. The removal rate calculation formula is: Removal rate = (A0-A1) / A0×100%; This experiment selected MB as a representative organic pollutant to participate in the experiment.

[0210] Energy consumption analysis refers to the electrical energy consumed in the process of treating pollutants by the electrochemical system. The energy consumption calculation formula is:

[0211]

[0212] Where: EC is energy consumption (kWh / kg); U is DC voltage (V); I is current (A); t is reaction time (h); V is total volume of reaction solution (L); C0 and C t are the pollutant concentrations in the water sample at the initial time and at time t (mg / L), respectively.

[0213] (1) Sn-Zn / AC particles prepared under different conditions and their MB removal rates

[0214] The following table lists the removal rates of MB by Sn-Zn / AC particles obtained under different preparation conditions. In the MB removal test, the experimental conditions were set as follows: cell voltage 5V, pH 4, electrolyte Na2SO4 concentration 20mmol / L, Sn-Zn / AC particle filling amount 2g, pollutant concentration 40mg / L, and catalytic time 15min.

[0215] Table 1 Particle preparation conditions and MB removal rate statistics

[0216]

[0217]

[0218] As can be seen from Table 1, under a wide range of calcination temperatures (400-650°C), Sn 4+ Concentration (0.05~0.6mol / L), Zn 2+ In the range of concentration (0.05-0.6 mol / L) and calcination time (1-5 h), the Sn-Zn / AC particles prepared in this application all showed excellent MB removal performance. This fully proves that the preparation process has high flexibility and stability, and can prepare particles with excellent catalytic performance under various conditions. However, due to the excessive calcination temperature in Comparative Example 1, the particles were excessively dispersed and a complete product was not successfully formed, resulting in the AC particles not being successfully loaded with SnO2 and ZnSnO3.

[0219] (2) Different metal ion loading Sn 4+ / AC particles and different catalytic systems for MB removal

[0220] The experimental conditions are: cell voltage of 5 V, pH of 4, electrolyte Na2SO4 concentration of 20 mmol / L, Sn-Zn / AC particle filling amount of 2 g, pollutant concentration of 40 mg / L, and catalytic time of 0 to 50 min.

[0221] First, by analyzing the MB removal rate of the particle electrodes prepared in Example 1 and Comparative Examples 6 to 10, it can be found that Fig.10 (a) It can be seen that the Sn-Zn / AC particles can achieve a 100% removal effect within 20 minutes. This is because the addition of Zn not only improves the densification of the SnO2 electrode, but also reduces the charge transfer resistance of the electrode. The ZnSnO3 formed by Sn and Zn has excellent charge transfer ability, which can improve the catalytic degradation rate of MB by the Sn-Zn / AC particle electrode; while the removal efficiency of the Sn-Zn electrode within 50 minutes is only 82%, because the Sn-Zn electrode has no AC particles as a carrier, which seriously reduces its contact area, thereby reducing its removal rate; Sn-V / AC particles, Sn-Mn / AC particles, Sn-Fe / AC particles, Sn-Cu / AC particles and Sn-Ag / AC particles can only achieve a 100% removal rate within 40 minutes, which is mainly due to the relatively low catalytic activity of these electrodes themselves. This low catalytic activity not only restricts the generation of active species, but also leads to a higher charge transfer resistance. Therefore, their charge transfer ability is limited and they cannot remove MB quickly.

[0222] Secondly, by comparing the removal effect of MB by the electrocatalytic system in Example 1 with Comparative Examples 2 to 4 ( Fig.10 (a) Within the catalytic time of 30 min, the removal efficiency of the direct electrocatalytic system (E) was 61.2%, the AC electrocatalytic system (E-AC) was 64.1%, the Sn / AC particle electrocatalytic system (E-Sn / AC) was 79.51%, and the Sn-Zn / AC particle electrocatalytic system (E-Sn-Zn / AC) was as high as 100%. The high removal efficiency of the E-Sn-Zn / AC system is attributed to the addition of SnO2 and ZnSnO3, which not only significantly improved the oxygen evolution potential and ·OH yield of the particles, but also reduced the charge transfer resistance and accelerated the removal of MB. In contrast, the removal efficiency of the E system was greatly reduced due to the lack of SnO2 and ZnSnO3 active components and AC particles with high specific surface area; the E-AC system increased the mass transfer rate due to the addition of AC particles, but the removal efficiency was still limited; the E-Sn / AC system increased the oxygen evolution potential and reduced the side reactions by introducing SnO2, and the MB removal efficiency was improved to a certain extent.

[0223] Further comparison of the energy consumption of the E system, E-Sn / AC system and E-Sn-Zn / AC system ( Fig.10 (b)), based on the removal of 80% MB, the E-Sn-Zn / AC system has the highest efficiency and the lowest energy consumption, taking only 9 min ( Fig.10(a)), energy consumption is 43.54KWh / kg. This is due to the fact that the addition of SnO2 and ZnSnO3 greatly improves the reaction rate of the particles and reduces energy consumption. The excellent charge transfer ability of ZnSnO3 reduces the resistance of Sn-Zn / AC particles, increases the oxygen evolution potential, and makes the particles easier to polarize to form microelectrodes, thereby reducing the oxygen evolution side reaction and promoting the generation of OH and SO4 - ·Generation. Under the synergistic effect of particles and active free radicals, MB was rapidly catalytically removed. In contrast, the E-Sn / AC system and the E system required longer time (40 min and 45 min) to achieve the same removal rate due to the lack of Zn and Sn-Zn, respectively.

[0224] (3) Comparison of the removal effects of Sn-Zn / AC particles on different organic pollutants

[0225] from Fig.11 It can be seen from the comparison that the Sn-Zn / AC particles in Example 1 also show better performance in removing different organic pollutants than the Sn / AC particles in Comparative Example 4. Specifically, the removal rates of Rhodamine B (RhB) and methyl orange by Sn-Zn / AC particles are as high as 100% and 95%, respectively, when the catalytic time is 50 minutes. In contrast, the removal rates of RhB and methyl orange by Sn / AC particles in Comparative Example 4 are 89% and 82%, respectively, at the same time. This comparison clearly shows that the removal rates of Sn-Zn / AC particles for different organic pollutants are generally higher than those of Sn / AC particles, thus highlighting the superior performance and wide applicability of Sn-Zn / AC particles.

[0226] (4) Active species in the electrocatalytic system

[0227] In order to determine the active free radical species involved in the activation of persulfate by Sn-Zn / AC particles, the persulfate activation system of Sn-Zn / AC particles was tested by electrospinning resonance spectroscopy (ESR). The experimental conditions were persulfate concentration of 2.5 mmol / L, particle dosage of 2 g, pH = 6, and SO4 - · and · OH capture test.

[0228] from Fig.12 It can be observed that at 5 min, a clear DMPO-·OH characteristic peak (1:2:2:1) appeared in the aqueous solution, which strongly confirmed the presence of ·OH in the reaction system. - · Characteristic peaks (appearing as sextet peaks of equal intensity). As the detection time goes by, ·OH and SO4 -The characteristic peak intensities of · gradually increased, indicating that the number of these two free radicals increased during the reaction.

[0229] (5) Electrocatalytic stability test of particles

[0230] The present invention conducts electrocatalytic stability tests on the particles prepared in Example 1 and Comparative Example 3 from four perspectives: linear sweep voltammetry (LSV), electrochemical impedance spectroscopy (EIS), Tafel slope, and cycle stability.

[0231] The test conditions for LSV were Princeton Versa STAT 4 electrochemical workstation, platinum electrode as counter electrode, Ag / AgCl electrode as reference electrode, 0.1 mol / L Na2SO4 solution as electrolyte, voltage window 0 V to 1.6 V, scan rate 10 mV / s, and MB concentration 10 mg / L; the test conditions for EIS and Tafel slope were Princeton Versa STAT 4 electrochemical workstation, the research sample was the working electrode, platinum electrode as counter electrode, Ag / AgCl electrode as reference electrode, 0.1 mol / L Na2SO4 solution as electrolyte, the test frequency range was 100 KHz-0.1 Hz, the AC amplitude was 10 mV, and the MB concentration was 10 mg / L.

[0232] First, LSV is to make the electrode potential change linearly from the starting potential to the ending potential at a certain potential scanning rate, and measure the current flowing through the working electrode at the same time. As the potential changes, the electrode surface undergoes redox changes, and the current also changes accordingly, which can be used to determine the oxygen evolution potential. In this study, the test results are as follows Fig.13 As shown, at a current density of 0.5 mA / cm 2 Under the condition of , the slope of the current-potential curve corresponding to the Sn-Zn / AC particles is much lower than that of the AC particles. The main reason for this difference is that the Sn-Zn / AC particles have a higher oxygen evolution overpotential, that is, in order to achieve the same current density, the Sn-Zn / AC particles require a higher potential. Therefore, under the same current density, the oxygen evolution potential of the Sn-Zn / AC particles is higher than that of the AC particles. This higher oxygen evolution overpotential helps to inhibit the occurrence of oxygen evolution side reactions, thereby improving the stability of the entire system.

[0233] Secondly, EIS measures the impedance of the electrode system at different frequencies to obtain a curve of impedance versus frequency, which reflects the resistance of the electrode system to alternating current. The semicircular arc in the high-frequency region (0-10KHz) mainly reflects the solution resistance and charge transfer resistance. The smaller the diameter of the semicircular arc, the smaller the charge transfer resistance of the particle. Fig.14As shown in the figure, the semicircular diameter of Sn-Zn / AC particles is smaller than that of AC particles, indicating that the charge transfer resistance of Sn-Zn / AC particles is smaller. Smaller charge transfer resistance can enable the electrode to maintain better performance during multiple cycles, reduce energy loss and performance degradation caused by increased resistance, and thus improve the stability of the electrode.

[0234] In addition, the Tafel slope describes the polarization of the electrode, and the change in overpotential is reflected by measuring the current density, that is, the Tafel slope, which can reflect the electron release rate. Fig.15 As shown, the slope of Sn-Zn / AC particles is lower than that of AC particles. A lower Tafel slope indicates a higher electron release rate, that is, the reaction kinetics of Sn-Zn / AC particles is faster, which is conducive to the stable existence of the system.

[0235] Finally, in order to further evaluate the cyclic stability of Sn-Zn / AC particles in the electrocatalytic system, five cycles of Sn-Zn / AC particles were conducted with MB as the target pollutant under the conditions of voltage of 5V, pH=3, Na2SO4 concentration of 20mmol / L, and particle dosage of 2g. The reaction time was set to 20min, and the particles were required to be adsorbed saturated before entering the reaction system. After the experiment, the particles were separated using a sieve and cleaned with ultrasonic and deionized water, and then dried in an oven at 60°C. All cycle tests were carried out under the same conditions.

[0236] from Fig.16 It can be seen that after adsorption saturation, the Sn-Zn / AC particles basically reached the adsorption equilibrium state. In the five cycle tests, the removal effect of the Sn-Zn / AC electrocatalytic system on MB remained stable, and the removal rate remained above 90%. This is mainly attributed to the high oxygen evolution potential and excellent charge transfer ability of the Sn-Zn / AC particles, which can quickly oxidize and remove pollutants adsorbed on the surface, thereby effectively slowing down the accumulation of pollutants on the particle surface.

[0237] The ICP test was performed on the solution after the Sn-Zn / AC particles were cycled five times and the solution after the Sn / AC particles were cycled once. The test results are shown in Table 2.

[0238] Table 2ICP test results

[0239]

[0240] It can be seen from Table 2 that in the first cycle experiment, the Sn in the Sn-Zn / AC particles 4+ and Zn 2+ The precipitation amounts of Sn and SnO reached the maximum values ​​of 420 μg / L and 838.5 μg / L respectively.4+ and Zn 2+ The precipitation amount gradually decreased, and after the fifth repeated experiment, the precipitation amount dropped to 350μg / L and 411.9μg / L respectively. This change can be attributed to the high content of metal oxides on the surface of the particles when they were first used, and the unstable loads were slightly detached due to collision during the reaction. At the same time, since Zn is more active than Sn and is more soluble in acidic solutions, Zn 2+ The dissolution amount is always greater than that of Sn 4+ It is worth noting that Zn 2+ The increase in Sn 4+ Compared with the Sn / AC particles without Zn addition, the Sn-Zn / AC particles have Sn 4+ The dissolution amount of Zn 2+ The anodic protection effectively inhibits Sn 4+ The dissolution of Sn / AC particles is enhanced. 4+ The dissolution amount of Sn-Zn / AC particles is as high as 1490 μg / L, which is the highest in the first cycle of Sn-Zn / AC particles. 4+ 3.548 times the dissolution amount.

[0241] In summary, the present invention combines the impregnation method and the calcination method to prepare Sn-Zn / AC particles, and successfully achieves Sn 4+ and Zn 2+ Good loading on the AC surface. Among them, AC exhibits high conductivity, stable chemical properties and excellent ability to generate active free radicals. The carrier not only loads the active component SnO2, but also contains a small amount of ZnSnO3. SnO2 is selected for its high oxygen evolution potential, excellent conductivity and chemical stability; and the loading of ZnSnO3 not only covers the surface of AC, but also penetrates into some internal gaps to form an anode protection layer. This protective layer effectively inhibits SnO2 from being absorbed by the surface of AC. 4+ The dissolution of SnO2 improves the densification of SnO2 and reduces the charge transfer resistance of the particle electrode, thereby significantly enhancing the charge transfer efficiency on the surface of Sn-Zn / AC particles. Under the action of the electric field, Sn-Zn / AC particles are more easily polarized to form microelectrodes. The increase of these microelectrodes and their higher oxygen evolution potential effectively inhibit the oxygen evolution side reaction during the reaction process, prompting the generation of more hydroxyl radicals (·OH) in the system, thereby improving the catalytic degradation and removal rate of organic pollutants including methylene blue, rhodamine B, and methyl orange by the electrocatalytic system constructed based on Sn-Zn / AC particles.

[0242] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A Sn-Zn / AC particle, characterized in that: The Sn-Zn / AC particles use activated carbon as a carrier and mainly load SnO2 and ZnSnO3.

2. The method for preparing Sn-Zn / AC particles according to claim 1, characterized in that: The steps include: adding activated carbon to a 4+ 、Zn 2+ After being fully impregnated in the impregnation solution, the Sn-Zn / AC particles are fully calcined at 400-650°C to obtain Sn-Zn / AC particles.

3. The preparation method according to claim 2, characterized in that: The Sn 4+ With Zn 2+ The molar ratio is 1:(0.083~12).

4. The preparation method according to claim 2, characterized in that: The preparation method of the impregnation solution comprises the following steps: 4+ 、Zn 2+ The solution is mixed with citric acid and alcohol solvent to obtain the impregnation solution.

5. The preparation method according to claim 2, characterized in that: The Sn 4+ The tin salt is selected from tin chloride, potassium stannate, sodium stannate or a hydrate of any of the above tin salts.

6. The preparation method according to claim 2, characterized in that: The Zn 2+ The zinc salt is selected from zinc nitrate, zinc sulfate, zinc chloride or a hydrate of any of the above zinc salts.

7. The preparation method according to claim 4, characterized in that: The alcohol solvent includes one or more of ethylene glycol, propylene glycol, and butylene glycol.

8. An electrocatalytic system, characterized in that: The electrocatalytic system comprises a cathode, an anode, a third electrode and an electrolyte, and the third electrode comprises the Sn—Zn / AC particles according to claim 1 .

9. Use of the Sn-Zn / AC particles according to claim 1 or the electrocatalytic system according to claim 8 in degrading and removing organic pollutants.

10. The use according to claim 9, characterized in that: The organic pollutants include one or more of methylene blue, rhodamine B, and methyl orange.

Citation Information

Patent Citations

  • Particle electrode for photocatalytic three-dimensional electrode / electro-Fenton system and preparation method thereof

    CN103739043A

  • Preparation method of active carbon loaded catalyst for electrochemically catalyzing and degrading organic wastewater

    CN105457643A

  • Preparation method of zinc stannate nanocube / graphene aerogel sunlight catalyst for degrading ciprofloxacin hydrochloride wastewater

    CN109675546A

  • Three-dimensional particle electrode with F-doped modified metallic oxide as catalyst and preparation method of three-dimensional particle electrode

    CN109967097A